A Two-Stage Method for Obtaining Reliable Teacher Assessments of Writing - Humphry, Stephen; Heldsinger, Sandy (Frontiers in Education, 2020)
In many countries, systems have employed externally imposed large-scale standardised assessments in seeking to obtain reliable and comparable assessments. To attain the same objectives while placing value on professional judgement, appropriate methods of assessment for classroom teachers need to be developed and tested. Accordingly, this paper examines the level of reliability of assessments made by classroom teachers of narrative writing using a two-stage classroom assessment method. The students involved in the study are primary students. The results show high levels of inter-rater reliability among teachers. The findings reproduce and expand on previous evidence indicating the two-stage method is a viable method of classroom teacher assessment of written performances. Implications of the results for assessment practices in education are discussed in light of background literature, with a focus on the widely expressed desire to value professional expertise.